IJCM_266A: Epidemiological Factors and Patterns of Unintentional Injuries In Children (0-14years), Admitted At A Tertiary Health Care Center, Jabalpur M.P - Raghuwanshi Rishika; Tiwari Rajesh; Tomar Akanksha (Wolters Kluwer Medknow Publications, 2024)
Background: Injuries are a leading cause of mortality among children, responsible for roughly one million deaths worldwide annually. Unintentional Injuries constitutes 90% of these. Southeast Asian region contributes to about one-third of all global injuries but there is paucity of data from our setting Objective: To describe the pattern, epidemiological factors and outcome of unintentional injuries among children aged 0-14 years reporting at a Tertiary Care Centre. Methodology: A prospective observational study was done among children with unintentional injuries admitted under NSCB medical college and hospital, Jabalpur, between Sep-Oct 2023. All children age. Results: Out of 66 cases admitted, majority were males (53.03% vs 46.97% females). Among all, animal related injuries were highest, followed by fall- related, road-traffic accidents, burn, trauma, poisoning and drowning. In-hospital mortality (12%) was reported among very few. Most common age group affected was 11-14 years and least among infants. Most of the injuries were occurred in home (50%) followed by streets & highways (30%). One third of all were polytraumatic cases. In RTA pillion rider were commonly get injury than front riders and walkers. Conclusion: The results can help in designing injury prevention strategies and awareness programs in similar settings.